Phenotypic Characterization and Distribution of Sensi-1 Agrinak Chicken - Sofjan Iskandar (Indonesian Center for Animal Research and Development, 2018)
The utilization of local chicken genetic resources in Indonesia is increasing after the government program to achieve food sovereignty including livestock products. In the year of 2017, the Indonesian Research Institute for Animal Production (IRIAP) released SenSi-1 Agrinak chicken breed to be used as commercial meat type of local chicken in Indonesia. This paper describes development and distribution of the SenSi-1 Agrinak. This breed was selected from the native breed of Sentul chicken, originated from Ciamis District of West Java Province. The Sentul male was selected to achieve average live weight of 1 kg/bird at 10 weeks of age, with grey (G) and black spotted white (BSW) plumage color and pea-comb type. After six generations of selection, SenSi-1 Agrinak was released as an improved local meat-type chicken breed. License to private local chicken breeders is expected to increase SenSi-1 Agrinak population and distribution. Collaboration with several Assessment Institutes for Agricultural Technology (AIAT) and implementation of #BEKERJA-Ministry of Agriculture program can accelerate population and distribution of SenSi-1 Agrinak chicken to farmers throughout Indonesia.